A BYSTANDER TO GENOCIDE1 : REVISITING UN FAILURE IN THE BALKANS AND RWANDA - Ariye, E.C. (European Scientific Journal, ESJ, 2015)
Against the backdrop of high expectations from the international community on the United Nations in the wake of the end of the Cold War and Super Power rivalries which had encumbered its performance over the years as a global institution capable of enthroning peace, this study revisits two episodes generally regarded as low points in the UN’s avowed peace purpose and efforts. Using a case study approach, the study interrogates the UN’s initiatives at Bosnia and Rwanda and concludes that in these instances, the global body failed institutionally to stop mass murders, rapes as well as destruction and desecration of cultural heritages. Indeed, it is argued strongly here that in Bosnia and Rwanda, the UN was merely, to borrow the words of Samantha Power,’ a bystander to genocide’